Intranasal Delivery of miR-146a Mimics Delayed Seizure Onset in the Lithium-Pilocarpine Mouse Model - Hua Tao; Jianghao Zhao; Tingting Liu; Yujie Cai; Xu Zhou; Huaijie Xing; Yan Wang; Mingkang Yin; Wangtao Zhong; Zhou Liu; Keshen Li; Bin Zhao; et al. (Mediators of Inflammation)
Unveiling the key mechanism of temporal lobe epilepsy (TLE) for the development of novel treatments is of increasing interest, and anti-inflammatory miR-146a is now considered a promising molecular target for TLE. In the current study, a C57BL/6 TLE mouse model was established using the lithium-pilocarpine protocol. The seizure degree was evaluated according to the Racine scale, and level 5 was considered the threshold for generalized convulsions. Animals were sacrificed to analyze the hippocampus at three time points (2 h and 4 and 8 weeks after pilocarpine administration to evaluate the acute, latent, and chronic phases, resp.). After intranasal delivery of miR-146a mimics (30 min before pilocarpine injection), the percent of animals with no induced seizures increased by 6.7%, the latency to generalized convulsions was extended, and seizure severity was reduced. Additionally, hippocampal damage was alleviated. While the relative miR-146a levels significantly increased, the expression of its target mRNAs (IRAK-1 and TRAF-6) and typical inflammatory modulators (NF-κB, TNF-α, IL-1β, and IL-6) decreased, supporting an anti-inflammatory role of miR-146a via the TLR pathway. This study is the first to demonstrate that intranasal delivery of miR-146a mimics can improve seizure onset and hippocampal damage in the acute phase of lithium-pilocarpine-induced seizures, which provides inflammation-based clues for the development of novel TLE treatments.